Menggali Nilai Pendidikan Karakter dalam Cerita Rakyat Punden: Kajian Sastra Lisan di Kecamatan Dukun Kabupaten Gresik: Exploring Character Education Values in the Folk Tale of Punden: An Oral Literature Study in Dukun District, Gresik Regency - Muttaqin, Khoirul; Umie Murniatie, Itznaniyah; Lailiyah, Fitrotul (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study examines the values of character education contained in Punden folklore in Dukun District, Gresik Regency. The object of the research is 5 punden stories in Shamun sub-districts located in the western, central, and eastern regions of the sub-district. The method used in this study is a qualitative descriptive research method that is more specifically in the form of ethnographic research. The determination of resource persons was carried out by snowball sampling. Data validation is carried out by theoretical triangulation. The data analysis technique was used descriptive and content analysis techniques. Based on the results of the study, it was found that through an analysis of 18 character values sourced from religion, Pancasila, culture, and national education goals, this punden story is loaded with these values, with only three values, love of the homeland, care for the environment, and love of reading, which are not identified. The values that emerge include religious attitudes, honesty, tolerance, discipline, hard work, creative, independent, democratic, curious, nationalistic, appreciative of achievements, communicative, peace-loving, social care, and responsibility. The results of the study show that Punden folklore can be used as an effective means to develop students' character. Therefore, it is recommended that punden stories in Dukun District be used as teaching materials in learning, with the development of appropriate teaching modules.